2012
DOI: 10.5194/hess-16-4467-2012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the physical controls of regional patterns of flow duration curves – Part 3: A catchment classification system based on regime curve indicators

Abstract: Abstract. Predictions of hydrological responses in ungauged catchments can benefit from a classification scheme that can organize and pool together catchments that exhibit a level of hydrologic similarity, especially similarity in some key variable or signature of interest. Since catchments are complex systems with a level of self-organization arising from co-evolution of climate and landscape properties, including vegetation, there is much to be gained from developing a classification system based on a compar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 32 publications
(38 reference statements)
4
80
0
Order By: Relevance
“…Second, the predictions at these locations are improved using machine learning techniques for error correction. Third, the classification system proposed by Coopersmith et al (2012) is used to generalize the parameters calibrated at each location, enabling its application at other sites characterized by the same hydroclimatic class. Fourth, sites are examined for edaphic (soil property) similarity in addition to hydroclimates.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the predictions at these locations are improved using machine learning techniques for error correction. Third, the classification system proposed by Coopersmith et al (2012) is used to generalize the parameters calibrated at each location, enabling its application at other sites characterized by the same hydroclimatic class. Fourth, sites are examined for edaphic (soil property) similarity in addition to hydroclimates.…”
Section: Methodsmentioning
confidence: 99%
“…If the hypothesis is correct, then the first type, when x and y fall within the same hydroclimatic class, should display limited losses in predictive power. The second type, when x and y fall within a "similar" hydroclimatic class (two classes differing by a single division of the classification tree developed in Coopersmith et al, 2012), should display greater losses of predictive power. Finally, the third type, when x and y fall in two unrelated classes, should display the largest loss of predictive power.…”
Section: Step 3: Estimation By Hydroclimatic Similaritymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent similarity studies have systematically analyzed large numbers of catchments focusing on streamfloworiented signatures such as the runoff coefficient, baseflow index, and slope of the flow duration curve and have then explored relationships between these signatures and model process timescales . Coopersmith et al (2012) generalized this work with four nearly orthogonal signatures that included aridity, seasonality of rainfall, peak rainfall, and peak streamflow and demonstrated that 77 % of MOPEX catchments can be described by only six classes, which are themselves defined by combinations of the four signatures. Clearly there is information contained in these catchment databases about not just the coevolution of climate (forcing) and landscape properties (parameters), but also the physics of the catchment responses.…”
Section: Data Requirementsmentioning
confidence: 99%